Critical Success Factors For Effective User-Centric Online Information System For Smart Government In UAE - Alkhoori, Khaled Husain Mohamed Shareed Abdullah; Mohd, Othman; Akmal, Suriati; Suhaimin, Nizam; Hakimi, Halimaton; Alhosni, Fahad Ismail Ahmed Khalifa (Journal of Applied Technology and Innovation, 2023)
The study investigated the factors that determine citizens’ expectations of smart government services in UAE. A survey method was used to collect data from 392 respondents. The data was analyzed using descriptive statistics (mean, standard deviation, and Relative Importance Index) and analysis of variance (ANOVA). The result revealed six factors that influence citizens’ expectations of smart government services: openness, responsiveness, transparency, trust, participation, and usability. It was found that all these factors are rated highly by the respondents, with transparency and trust being the most important ones. Furthermore, it was found that there is no significant difference in the expectations of smart government services across different age groups of respondents. It is recommended that smart government services should be designed and delivered in a way that meets the high expectations of citizens and enhances their satisfaction and trust.